2018
DOI: 10.1177/1120700018772047
|View full text |Cite
|
Sign up to set email alerts
|

Curved periacetabular osteotomy via a novel intermuscular approach between the sartorius and iliac muscles

Abstract: In addition to demonstrating a similarly satisfactory correctional angle, IM-CPO is anticipated to enable early weight-bearing and recovery of walking ability. Thus, IM-CPO is considered a superior surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…By binding to plasminogen, TXA prevents the conversion of plasminogen to plasmin, thus preventing fibrinolysis[ 4 ]. The use of TXA reduces blood loss and blood transfusion in major orthopedic surgery, and the safety is also well recognized[ 5 - 8 ]. Previous studies have not confirmed any increased risk of thromboembolism after the use of TXA in various surgeries[ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…By binding to plasminogen, TXA prevents the conversion of plasminogen to plasmin, thus preventing fibrinolysis[ 4 ]. The use of TXA reduces blood loss and blood transfusion in major orthopedic surgery, and the safety is also well recognized[ 5 - 8 ]. Previous studies have not confirmed any increased risk of thromboembolism after the use of TXA in various surgeries[ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidences of complete or incomplete LFCN injury have been reported from 30 to 63% with different surgical approaches [ 1 , 6 ], and a system review shown the rate of complete LFCN injury was 6.14% [ 4 ]. LFCN nerve injury has been reported to be around 30% after a modified S-P approach [ 14 ], about 10.5% after a modified Ollier approach [ 5 ], about 14% after an anterior intrapelvic approach [ 21 ], and about 6.7% [ 24 ] after the operative techniques initially described by Ganz et al [ 7 ]. When the tension induced by traction or compression is applied to a nerve, both the extrinsic and intrinsic vascular supplies would affect the neural ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The Tönnis classification of hip osteoarthritis [ 16 , 17 ] was used to grade osteoarthritis, and the Hartofilakidis classification system [ 18 , 19 ] was used to assess the dysplastic hip. The indications for acetabulum osteotomy include symptomatic hip dysplasia that persists for more than 6 months after nonsurgical treatment failure, center–edge angle of Wiberg (LCE angle) < 25°, acetabular index (AI) > 10°, Tönnis grade 0–1, Y-type epiphyseal cartilage closure, and younger than 50 years of age [ 14 , 20 , 21 ]. Furthermore, the inclusion criteria included: (I) acetabular reorientation surgery with the use of Bernese PAO, (II) using the modified S-P or Bikini approach with posterolateral assisted incision.…”
Section: Methodsmentioning
confidence: 99%
“…A critical, intraoperative assessment of the flexion and internal rotation of the hip joint must be performed in every case. Some authors believe less invasive approaches for PAO to be unsuitable to perform a simultaneous arthrotomy for addressing femoral neck pathologies [14,22]. Our described technique for RASS PAO allows for easy arthrotomy, to perform femoral head-neck offset correction via the used Smith-Peterson or Hueter approach, which has been described primarily in 1882 [23].…”
Section: Discussionmentioning
confidence: 99%